2018
DOI: 10.1101/370239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Base-pairing requirements for small RNA-mediated gene silencing of recessive self-incompatibility alleles inArabidopsis halleri

Abstract: both SRK alleles were expressed at similar levels in all 36 heterozygote genotypes. We show that the base-pairing 37 requirements for effective transcriptional silencing by these sRNAs 38 are broadly similar to those of canonical microRNAs, even though 39 they are believed to function in sharply different ways. We discuss 40 the implications for the evolutionary processes associated with the 41

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…CC-BY-NC-ND 4.0 International license a certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made available under The copyright holder for this preprint (which was not this version posted March 3, 2020. ; https://doi.org/10.1101/370239 doi: bioRxiv preprint and is quickly degraded as the development of pollen grains inside the anther progresses (Murphy & Ross, 1998;Takayama et al, 2000). We confirmed that differences exist in the temporal dynamics of expression among alleles, as suggested by Kusaba et al (2002) in A. lyrata, possibly as the result of strong sequence divergence of the promotor sequences of the different SCR alleles.…”
Section: Expression Profilesupporting
confidence: 72%
See 1 more Smart Citation
“…CC-BY-NC-ND 4.0 International license a certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made available under The copyright holder for this preprint (which was not this version posted March 3, 2020. ; https://doi.org/10.1101/370239 doi: bioRxiv preprint and is quickly degraded as the development of pollen grains inside the anther progresses (Murphy & Ross, 1998;Takayama et al, 2000). We confirmed that differences exist in the temporal dynamics of expression among alleles, as suggested by Kusaba et al (2002) in A. lyrata, possibly as the result of strong sequence divergence of the promotor sequences of the different SCR alleles.…”
Section: Expression Profilesupporting
confidence: 72%
“…It is made available under The copyright holder for this preprint (which was not this version posted March 3, 2020. ; https://doi.org/10.1101/370239 doi: bioRxiv preprint et al, 2006). Furthermore, the position of mismatches along the microRNA:target duplex also seems to be crucial, with a greater tolerance in the 3' than the 5' region of the microRNA (up to four mismatches generally have limited functional consequences in the 3' region, while only two mismatches in the 5' region seem sufficient to abolish the target recognition capability; Liu et al, 2014, Mallory et al, 2004Parizotto et al, 2004;Schwab et al, 2005). These observations have led to the formulation of general "rules" for microRNA targeting (Axtell & Meyers, 2018), but at the same time they also revealed a large number of exceptions.…”
Section: Introductionmentioning
confidence: 99%
“…4b ). We found one potential target region of CbpBmirS3 sRNA in the C. grandiflora derived subgenome A S -locus of C. bursa-pastoris with an affinity >18 (Durand et al 2014 ; Burghgraeve et al 2018 ), within 2 kb of the closest BLAST hit of SCR (Fig. 4d , e).…”
Section: Resultsmentioning
confidence: 83%
“…We used Trimmomatic v0.36 for removing sequencing adapters and for quality filtering of reads, before mapping small RNA of 18–27 nt length with STAR v2.5.3a (Dobin et al 2013 ) to an adjusted genome of C. rubella (Slotte et al 2013 ), where the C. rubella S -locus was replaced with a C. bursa-pastoris subgenome A or B S- locus, as in Bachmann et al ( 2019 ), and the annotation of identified sRNA precursors predicted above. To identify targets of expressed candidate sRNA dominance modifiers, we used a modified Smith and Waterman algorithm (Smith and Waterman 1981 ) as in Durand et al ( 2014 ) with the following scoring matrix: matches = +1; mismatches = −1; gaps = −2; G:U wobbles = −0.5 and a cutoff score for identifying targets of 18 (Burghgraeve et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…c). The sRNA target affinity was similar to that of functional Arabidopsis dominance modifiers (Durand et al ., ; Burghgraeve et al ., ). As expected if ComirS3 sRNAs silence C. grandiflora SCR , C. grandiflora SCR was specifically downregulated in S‐ locus heterozygotes (Fig.…”
Section: Resultsmentioning
confidence: 97%